Prevalence of Childhood Obesity and its PreventionSystematic Review - Ranjana Chavan1, Mangesh Jabade2 , Dipali Dumbre2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: Childhood obesity is one of the most serious public health challenges of the 21st centuryand prevalent global public health issue as children. The number of overweight or obese infants and youngchildren (aged 0 to 5 years) increased from 32 million globally in 1990 to 41 million in 2016. Overweight andobese children are likely to stay obese into adulthood and more likely to develop non communicable diseaseslike diabetes and cardiovascular diseases at a younger age. Therefore Prevention of childhood needs highpriority. Material & Methods: 125 citations in PubMed & ISI Web of science found by electronic search andfinally 19 articles were selected for writing systemic review. The search strategy consisted of search stringscomposed of terms targeting: prevalence, childhood obesity, prevention we restricted the search to articlespublished since 2012 to appropriate balances feasibility of implementation and the validity of the resultinginformation. Result: The prevalence of overweight and obesity among children and adolescents aged 5-19has risen dramatically from just 4% in 1975 to just over 18% in 2016. (WHO, 2017). Somewhere between5.74 percent and 8.82 percent of school children in India are obese. In China, the overweight and obesityrate in children aged 7 and over was 12.2% and 7.3%, respectively. Four different studies were screenedwhich was focused on at least one components like physical activity, physical fitness, fruit consumption.Significant changes observed on sedentary time (Watching TV and studying), active play time and fruitconsumption but there was no effect on BMI or the prevalence of Overweight/ Obesity. A family BasedObesity prevention programme is effective strategy to prevent childhood obesity by providing physicalactivity classes to improve behavior and skills of the children. Conclusion: The strength of evidence isstated that family based intervention plays pivotal role in preventing Childhood obesity